Paternal Low-Level Mosaicism-Caused SATB2-Associated Syndrome - Qian, Yeqing; Liu, Jiao; Yang, Yanmei; Chen, Min; Jin, Chunlei; Chen, Penglong; Lei, Yongliang; Pan, Hangyi; Dong, Minyue (Frontiers in Genetics, 2019)
Mutations of SATB2 (OMIM#608148) gene at 2q33.1 have been associated with the autosomal dominant SATB2-associated syndrome (SAS), which is still short of comprehensive diagnosis technologies for small deletions and low-level mosaicism. In this Chinese Han family, SNP-array identified a 4.9 kb deletion in the SATB2 gene in two consecutive siblings exhibiting obvious mental and developmental retardation and dental abnormalities, but failed to find so in their parents. Prenatal diagnosis revealed that their third child carried the same deletion in SATB2 and the pregnancy was terminated. To determine the genetic causes behind the inheritance of SATB2 deletion, gap-PCR was performed on peripheral blood-derived genomic DNA of the family and semen-derived DNA from the father. Gap-PCR revealed the deletions in the two affected siblings were inherited from the father while the less intense mutant band indicated the mosaicism of this mutation in father. The deletion was 3,013 bp in size, spanning from chr2: 200,191,313-200,194,324 (hg19) and covering the entire exon 9 and part of intron 8 and 9 sequences. Droplet digital PCR demonstrated mosaicism percentage of 13.2% and 16.7% in peripheral blood-derived genomic DNA and semen-derived DNA of the father, respectively. Hereby, we describe a family of SAS caused by paternal low-level mosaicism and provide effective diagnostic technologies for intragenic deletions.